1995
DOI: 10.1177/104973239500500207
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sexual Risk Behavior from Drug Users' Accounts of their Life Experiences

Abstract: This article attempts to place drug users' HIV-related risk behaviors in the context of their past and current life experiences. The presented material was taken from interviews of 228 drug users on their sexual attitudes and behaviors. Many clients reported traumatic and abusive childhoods, relationship and sexual difficulties, multiple losses of significant others, and social isolation. It is proposed that sexual risk behavior may be understood and explained in the context of clients' perception of themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Nonetheless, one of the most frequently cited outcomes associated with childhood maltreatment is an apparent increase in risk for drug abuse. Indeed, numerous studies have reported a relationship between childhood victimization experiences and substance abuse, with the majority of these studies focusing on sexual abuse (Bartholow et al, 1994; Bennett & Kemper, 1994; Benward & Densen-Gerber, 1975; Brown & Anderson, 1991; Cavaiola & Schiff, 1989; Duncan, Saunders, Kilpatrick, Hanson, & Resnick, 1996; Dunn, Ryan, & Dunn, 1994; Glover, Janikowski, & Benshoff, 1995; Gomes-Schwartz, Horowitz, & Sauzier, 1985; Hatzichristou & Papadatos, 1993; Hussey & Singer, 1993; Hussey, Strom, & Singer, 1992; Johnsen & Harlow, 1996; Kang, Magura, & Shapiro, 1994; Ladwig & Anderson, 1989; Morrow & Sorell, 1989; Rotheram-Borus, Mahler, Koopman, & Langabeer, 1996; Runtz & Briere, 1986; Sansonnet-Hayden, Haley, Marriage, & Fine, 1987; Sheridan, 1995; N. Singer, 1995; Teets, 1995).…”
mentioning
confidence: 99%
“…Nonetheless, one of the most frequently cited outcomes associated with childhood maltreatment is an apparent increase in risk for drug abuse. Indeed, numerous studies have reported a relationship between childhood victimization experiences and substance abuse, with the majority of these studies focusing on sexual abuse (Bartholow et al, 1994; Bennett & Kemper, 1994; Benward & Densen-Gerber, 1975; Brown & Anderson, 1991; Cavaiola & Schiff, 1989; Duncan, Saunders, Kilpatrick, Hanson, & Resnick, 1996; Dunn, Ryan, & Dunn, 1994; Glover, Janikowski, & Benshoff, 1995; Gomes-Schwartz, Horowitz, & Sauzier, 1985; Hatzichristou & Papadatos, 1993; Hussey & Singer, 1993; Hussey, Strom, & Singer, 1992; Johnsen & Harlow, 1996; Kang, Magura, & Shapiro, 1994; Ladwig & Anderson, 1989; Morrow & Sorell, 1989; Rotheram-Borus, Mahler, Koopman, & Langabeer, 1996; Runtz & Briere, 1986; Sansonnet-Hayden, Haley, Marriage, & Fine, 1987; Sheridan, 1995; N. Singer, 1995; Teets, 1995).…”
mentioning
confidence: 99%